2017
DOI: 10.2147/ijgm.s131768
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and outcomes of necrotizing soft tissue infections

Abstract: BackgroundNecrotizing soft tissue infections (NSTIs) are aggressive infections associated with significant morbidity, including amputation and organ failure, and high mortality. The rapid progression and significant risk of morbidity and mortality associated with NSTIs makes quick diagnosis and treatment critical. The objective of this study was to determine the presentation of patients diagnosed with NSTIs and their in-hospital outcomes.MethodsThis was a retrospective review of adult (>17 years) patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
5
20
0
Order By: Relevance
“…In our study, LRINEC score > 8 showed a statistically significant difference between mortality of the primary and late amputation groups. Chen et al identified vascular disease as a common comorbidity of necrotizing soft tissue infections [14]. On the basis of this study, we found that peripheral artery disease was an important independent factor associated with mortality in late amputation.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, LRINEC score > 8 showed a statistically significant difference between mortality of the primary and late amputation groups. Chen et al identified vascular disease as a common comorbidity of necrotizing soft tissue infections [14]. On the basis of this study, we found that peripheral artery disease was an important independent factor associated with mortality in late amputation.…”
Section: Discussionsupporting
confidence: 56%
“…23 NSTI appears to more commonly affect individuals with significant chronic health issues. 24 Most common comorbidities include diabetes mellitus, 4,[25][26][27][28] immunocompromise, [29][30][31] peripheral arterial disease, 30,32 obesity, 28,33 chronic liver disease, 7,34,35 malignancy, 32,36,37 and organ transplantation. [38][39][40] Otherwise healthy individuals developing NSTIs triggered by elective medical procedures, 41 medication injections or vaccinations, 42,43 or minimal trauma 20 have also been reported.…”
Section: Epidemiologymentioning
confidence: 99%
“…Conditions associated with NF include diabetes mellitus, renal insufficiency, arterial occlusive disease, intravenous drug abuse, body mass index > 30 kg/m², age > 65 years, liver disease, immunosuppression, recent surgery, and traumatic wounds or incision of the skin including minor lesions such as insect bites and injections sites [2][3][4]. NF has been classified into four types depending on microbiological findings: type I is of polymicrobial aetiology, including aerobic and anaerobic organisms; type II is caused by group A streptococci (GAS), either alone or in association with staphylococci; type III is represented by monomicrobial infections attributable to Clostridium species or Gram-negative bacteria; type IV is of fungal aetiology [1,5].…”
Section: Necrotising Fasciitis: An Overviewmentioning
confidence: 99%